(untitled) (World Bulletin of Social Sciences, 2022)
The article envisages the study of the genre structure and artistic features of poems in Navoi , the scope of the scholar’s creative heritage, the identification of artistic and stylistic features of prose works, the image of Navoi piri komil Abdurahmon Jami, the peculiarities of the spiritual world